ЛИБЕРАЛЬНАЯ „ЦАНКОВИСТСКАЯ“ ПАРТИЯ В УСЛОВИЯХ СТАМБОЛОВИСТСКОГО РЕЖИМА 1887–1894 гг.: ОСНОВНЫЕ НАПРАВЛЕНИЯ ДЕЯТЕЛЬНОСТИ - Крютченко, М. Л. (Дриновський збірник, 1970)
The article discusses the inner political situation in Bulgaria in the years 1887–1894, and also the analysis of the main activities of the political group of the Tsankovists during the S. Stambolov’s leadership. The author concludes that despite the establishment of Stambolov dictatorship, political activity of “moderate” liberals did not stop, but due to the emigration of its leaders had no significant effect on the political situation in Bulgaria.